P0889TO WHAT EXTENT CAN WE ACHIEVE MINERAL BONE METABOLISM TREATMENT TARGETS AS SUGGESTED BY UPDATED 2017 KDIGO GUIDELINES IN PATIENTS WITH PREDIALYSIS CHRONIC KIDNEY DISEASE. (6th June 2020) - Dincer, Mevlut Tamer; Özcan, Şeyda Gül; Alagoz, Selma; Karaca, Cebrail; Gulcicek, Sibel; Trabulus, Sinan; Pekpak, Meltem; Seyahi, Nurhan
Abstract: Background and Aims: The mineral bone disorder is an essential problem in chronic kidney disease (CKD). It is an independent modifiable risk factor for renal damage progression and CKD related mortality. Therefore, it is important to treat chronic kidney disease mineral bone disorder (CKD-MBD) according to international guidelines. Data on the management of mineral bone disorders in predialysis patients is scarce. We aimed to investigate the proportion of CKD-MBD patients reaching targets suggested by the updated 2017 KDIGO guidelines. Method: We performed a multicenter cross-sectional study. We recruited consecutive adult (>18 years of age) CKD 3-5 patients who were on regular nephrology outpatient clinic follow up. Patients who have GFR loss over 30% in the last six months, patients with malignancy, and decreased life expectancy due to severe comorbid disease and patients on renal replacement therapy were excluded. Data were collected in two-time points: one during the recruitment (second data point) and one, three to six months prior to the current visit (first data point). Persistent laboratory abnormalities were defined by out of normal range values in both time points. Therapeutic inertia was calculated for hyperphosphatemia. It was defined as a lack of using phosphate binders despite hyperphosphatemia. Results: We examined a total of 213 patients for 3 different nephrology outpatient clinics. Of these patients, 49.5 % were male, with a mean age of 64, 9 ± 12, 0 years. 51.7 % of the patients were diabetic, 78 % were hypertensive, and 20.1 % had a history of coronary artery disease. Laboratory values related to MBD are shown in Table 1. KDIGO guideline targets were not reached in 14.8%, 18.4%, 59.0%, 71.0% patients regarding Ca, P, PTH, and vitamin D in the first visit. The targets were not reached in 15.0%, 19, 2%, 61, 2%, 81% patients regarding Ca, P, PTH, and vitamin D in the second visit. Persistence of out of target values were observed in 5.8%, 9.9%, 49.2% and 65.4% of the patients for Ca, P, PTH and Vitamin D respectively. The prevalence of therapeutic inertia for hyperphosphatemia was 34, 4 % in the second visit Conclusion: Regarding KDIGO guidelines, MBD is not optimally managed in predialysis CKD patients. Clinicians should have an active attitude regarding the correction of MBD even at the earlier stages of CKD.